Herpetologia Segundo as Herpetólogas: A breath of female representation in Brazilian science - Vasconcelos, Beatriz Diogo; Vitoria Costa Rodrigues, Ana Paula; Albano de Mello, Anna Virginia; Santana Cassini, Carla; Araújo Salvino, Clara; Gennari Pires de Toledo, Daniela; Fenker, Jéssica; Albuquerque Pereira, Jessica; Rodrigues Vieira de Alencar, Laura; Gomes de Souza, Lucy; Basto da Silva, Marcélia; Ferreira Torello Viera, Natália; et al. (Herpetologia Brasileira, 2026)
Scientific dissemination plays a fundamental role in establishing the dialogue between science and the scientist with the citizen. The ‘Herpetólogas Segundo as Herpetólogas’ (H2H; English translation – Herpetology According to Women Herpetologists) initiative appears in a scenario where women are not recognized or encouraged in Science, Technology, Engineering, and Mathematics - STEM, feeling insecure and intimidated in their academic career. These feelings often impair women’s career continuity. In addition, gender gap in Brazilian herpetological community reflects unconscious perceptions of sexist stereotypes and the lack of references or role models. At the same time that the gender gap in STEM is a hot topic of discussion, Brazilian government is threatening progress of science in the country. There is a need to develop actions to disseminate research on herpetology and educate the population on the Brazilian herpetofauna (amphibians and reptiles). When the role of women herpetologists is promoted, it generates greater representation so that young researchers, women, and other transfeminine minorities feel encouraged to dedicate themselves to science. To this end, the H2H initiative promotes research and other initiatives that involve the participation of at least one Brazilian herpetologist and elaborates several social media posts with themes on environmental education and herpetofauna. These publications have a colloquial and didactic character accessible to a diverse audience but always maintaining scientific rigor. The popularization of studies in herpetology and the reduction of prejudice against herpetofauna in Brazil, in addition to the reduction of gender bias in science, can lead to increased diversity in research groups and contribute to more effective and inclusive science.